2020
DOI: 10.1007/s11104-020-04653-7
|View full text |Cite|
|
Sign up to set email alerts
|

Imaging plant responses to water deficit using electrical resistivity tomography

Abstract: Background and aims Monitoring root water uptake dynamics under water deficit (WD) conditions in fields are crucial to assess plant drought tolerance. In this study, we investigate the ability of Electrical Resistivity Tomography (ERT) to capture specific soil water depletion induced by root water uptake. Methods A combination of surface and depth electrodes with a high spatial resolution (10 cm) was used to map 2-D changes of bulk soil electrical conductivity (EC) in an agronomic trial with different herbac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Overall, ERT may lack direct sensitivity to root properties due to the variations in the contrast between bulk soil and root electrical resistivity and the relatively low volume fraction of roots. Using resistivity as a predictor for root biomass without taking these factors into account is therefore highly uncertain (Rao, Lesparre, Orozco, Wagner, & Javaux, 2020).…”
Section: Ertmentioning
confidence: 99%
“…Overall, ERT may lack direct sensitivity to root properties due to the variations in the contrast between bulk soil and root electrical resistivity and the relatively low volume fraction of roots. Using resistivity as a predictor for root biomass without taking these factors into account is therefore highly uncertain (Rao, Lesparre, Orozco, Wagner, & Javaux, 2020).…”
Section: Ertmentioning
confidence: 99%
“…It is however worth mentioning that this pedophysical model is only valid for bare soil. Therefore, if future studies consider soil with roots, additional uncertainty arises and needs to be addressed (Rao et al., 2020; Werban, Al Hagrey, & Rabbel, 2008). In addition, one must consider that an ERT model can show misleading variability due to factors contributing to its uncertainty, such as regularization, error model, and inversion related artifacts (different electrode contact impedance, finite electrode size).…”
Section: Resultsmentioning
confidence: 99%
“…where d is the data vector, m is the model given by the parameters of the inversion m j = log(ρ j ) (Ω m), f(m), is the forward model for parameters m, m 0 is a homogeneous starting model vector, W ε is a smoothing operator, λ is the regularization parameter that determines the amount of smoothing imposed on m, and W s is an error weighting matrix. We acknowledge the importance of choosing appropriate regularization parameters for accurate inversion results (Rao, Lesparre, Orozco, Wagner, & Javaux, 2020). After a series of synthetic model simulations, we concluded that 100 is an appropriate value for λ.…”
Section: Ert Monitoring and Inversionmentioning
confidence: 89%
See 1 more Smart Citation
“…Great progress has been made over the past decade to combine geophysical observation data with hydrological models (Camporese et al, 2010(Camporese et al, , 2011Tso et al, 2020). Relatively few hydro-geophysical applications, though, have been focused on root system parametrization (Manoli et al, 2015;Cassiani et al, 2016;Mary et al, 2020;Rao et al, 2020). In a series of studies, (Kuhl et al, 2018), Kuhl et al (2021) propose a novel coupled hydrogeophysical approach to estimate evapotranspiration (ET) and root depth from ER, and soil water content combining both soil water content from Time Domain Reflectometry (TDR) and ER measurements with a hydrological and plant model.…”
mentioning
confidence: 99%